Edukasi Energi Bersih dan Penerapan Panel Surya di lingkungan HKBP Aek Bolon, Balige, Kabupaten Toba - Verdinand Robertua; Arthuur Jeverson Maya; Sinta Herindrasti; Adrianus Lengu Wene (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
The Community Service Program (PKM) entitled "CLEAN ENERGY EDUCATION AND SOLAR PANEL APPLICATION AT THE HKBP AEK BOLON CHURCH" in the Aek Bolon Julu Village, Balige District, Toba Regency, demonstrated the commitment of the PKM team to raise awareness and utilize solar energy. Cooperation with the Pomparan Opung Jaenna Siahaan indigenous community provided significant financial and logistical support, including funding for the construction of solar panel lamp foundation poles, location permits, as well as transportation and accommodation for the PKM implementation team. The impact was not only seen in cost savings for the Church and its congregation but also in optimizing the Church hall asset, which could then be used more effectively at night. Before the solar panel lighting, fear and limited access to the Church at night were the main obstacles. Through educational activities such as lectures during worship days, the PKM team succeeded in increasing the Church community's awareness of sustainable solutions. This program not only provided improvements in infrastructure but also created a safe and comfortable environment, reflecting the positive impact directly felt by the community around the HKBP AEK BOLON Church.